REVISI AMPELOCISSUS DI SUMATRA - Syadwina Hamama Dalimunthe; Tatik Chikmawati; Elizabeth A. Widjaja (PTTI, 2016)
Syadwina Hamama Dalimunthe, Tatik Chikmawati & Elizabeth A. Widjaja. 2016. Revision of Ampelocissus (Vitaceae) in Sumatra. Floribunda 5(5): 165–174. — This study has been done by observing the morphological characters of 83 herbarium specimen collection numbers. Ten species and one variety are found in Sumatra, namely seven species from previous study (A. arachnoidea, A. gracilis, A. korthalsii, A. imperialis, A. ochracea, A. polythyrsa, and A. thyrsiflora) three species and one variety are newly recorded (A. elegans, A. filipes, A. rubiginosa, and Ampelocissus ochracea var. trilobata). Identification key, nomenclature, synonym, morphological descriptions, distribution, examined specimens, and similarity analysis of Ampelocissus species is presented.Keywords: Ampelocissus, morphology, revision, Sumatra.Syadwina Hamama Dalimunthe, Tatik Chikmawati & Elizabeth A. Widjaja. 2016. Revisi Ampelocissus (Vitaceae) di Sumatra. Floribunda 5(5): 165–174. — Penelitian ini telah dilakukan dengan mengamati ciri morfologi dari 83 nomor koleksi spesimen herbarium. Sepuluh jenis dan satu varietas ditemukan di pulau ini, yakni, tujuh jenis sesuai dengan studi sebelumnya (A. arachnoidea, A. gracilis, A. korthalsii, A. imperialis, A. ochracea, A. polythyrsa, A. thyrsiflora) serta tiga jenis dan satu varietas rekaman baru (A. elegans, A. filipes, A. rubiginosa, dan Ampelocissus ochracea var. trilobata). Kunci identifikasi, tata nama, sinonim, deskripsi morfologi, sebaran, spesimen yang diamati, dan analisis keserupaan jenis-jenis dalam marga Ampelocissus disajikan.Kata kunci: Ampelocissus, morfologi, revisi, Sumatra.